2008
DOI: 10.1002/app.27601
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and structure of a polyamide/silver iodide nanocomposite

Abstract: In this study, the structure and properties of an organic-inorganic composite material, prepared from nylon 6 doped with fine particles of silver iodide (AgI), were examined. The preparation of the composite involved the complexation of nylon 6 with polyiodide ions such as I 3 -and I 5 -by immersion in an iodine-potassium iodide (I 2 -KI) aqueous solution followed by reaction in an AgNO 3 aqueous solution, resulting in the in-situ formation of β-AgI fine particles within the nylon 6 matrix. The AgI content for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…50wt% of the total composite weight. As shown in our previous work [31], AgI easily forms in the bulk nylon 6 matrix. Thus, the AgI component is considered to exist both on the surface and inside the nanofiber.…”
Section: Measurementssupporting
confidence: 71%
See 1 more Smart Citation
“…50wt% of the total composite weight. As shown in our previous work [31], AgI easily forms in the bulk nylon 6 matrix. Thus, the AgI component is considered to exist both on the surface and inside the nanofiber.…”
Section: Measurementssupporting
confidence: 71%
“…1×10 Fabrication of silver plated nylon 6 nanofibers using iodine We have previously reported a method to impart metal iodides into a polymer matrix by utilizing the affinity of iodine to various kinds of polymers to prepare organic/inorganic composites. For example, some polymers form complexes with polyiodide ions, and silver iodide and copper iodide can be precipitated in situ in polymer matrices by the reaction of polyiodide ions with metal ions [30,31]. The metal iodides thus introduced can be converted to metal particles in the composite by using a reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…The Ag/silicone composite membranes were prepared using the following method, which is a modification of the procedure described by Fujimori et al 2008 . A 0.3-mm thick silicone membrane ASONE, Osaka, Japan was cut into 50 mm 50 mm pieces.…”
Section: Preparation Of Ag/silicone Composite Membranesmentioning
confidence: 99%
“…They reported that a prolonged antibacterial effect was silicone used to construct the membrane. Fujimori et al 2008 also doped AgI into nylon 6 by immersion in an iodide solution, followed by silver nitrate AgNO 3 treatment to improve the fiber conductivity. In addition, the composite fiber exhibited antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…6 An organic-inorganic composite material was prepared from nylon 6 doped with fine particles of silver iodide, and it was observed that the film had high antibacterial properties. 7 Due to complications in processing of fiber and production of film, the majority of researches on polymer/ silver nano-composite, similar to the above mentioned, have focused on molded bulk materials that suffer from many demerits, whereas this research has given special attention to the design of an environmentally friendly technique and also offers the opportunity to prepare polymer/silver multifilament yarns on a large scale without the usage of solvents or carriers. Moreover, since the active agent is physically embedded in the structure of the fiber and released slowly during usage, this method provides the best durability.…”
Section: Introductionmentioning
confidence: 99%